Предмет: Алгебра,
автор: msmarif
решить уравнение способом подстановки 2 (х-у)+3 (х+у)=39 3(х-у)-2 (х+у)=-13 РЕШИТЕ ПОЖАЛУЙСТА
Ответы
Автор ответа:
0
2х-2у+3х+3у=39
3х-3у-2х-2у= -13
5х+у=39
х-5у== -13
у=39-5х
х-5у= -13
у=39-5х
х-5(39-5х)= -13
у=39-5х
х-195+25х= -13
у=39-5х
26х=182
у=4
х=7
3х-3у-2х-2у= -13
5х+у=39
х-5у== -13
у=39-5х
х-5у= -13
у=39-5х
х-5(39-5х)= -13
у=39-5х
х-195+25х= -13
у=39-5х
26х=182
у=4
х=7
Автор ответа:
0
Спасибо большое!
Похожие вопросы
Предмет: Математика,
автор: valeraspirkin3
Предмет: Математика,
автор: briaizake
Предмет: Математика,
автор: yaroslavkuzmenok
Предмет: Математика,
автор: Kotyam
Предмет: Математика,
автор: ziyarat12345